Five New Records of Ants (Hymenoptera: Formicidae) From Morocco. Issue 1 (5th April 2015) - Taheri, Ahmed; Reyes-López, Joaquin L.
Abstract : A recent catalogue of the rich ant fauna of Morocco included 214 species, with later studies adding an additional 12 species. Following recent fieldwork in the north of Morocco, we report five new records for the country ( Plagiolepis pygmaea Latreille, 1798, Ponera testacea Emery, 1895, Strumigenys tenuipilis Emery, 1915, Temnothorax pardoi Tinaut, 1987, and Tetramorium parvioculum Guillem & Bensusan, 2009) and we present new data on the distribution and natural history of six additional species. This work brings the total number of ants known from Morocco to 233, taking into account two species which were omitted in the list of Cagniant.